Factors Affecting Tax Aggressiveness in Manufacturing Companies in The Consumer Goods Industry Subsector - Dewi Fortuna Aman; Ngurah Pandji Mertha Agung Durya (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
Tax aggressiveness is an act that can be carried out both legally and illegally with the intention of reducing tax costs imposed through tax planning activities. This study was conducted with the aim of knowing the effect of capital intensity, profitability, leverage, firm size and inventory intensity on tax aggressiveness in consumer goods industry sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The population used in this study were 64 companies. The research sample obtained was 20 companies, where the sampling used purposive sampling technique and the amount of data collected in this study was 60 data. The data source used is secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange (IDX) and the type of data used in this study is quantitative. The data analysis tool used is IBM Statistical Product and Service Solutions (SPSS) version 20. Data analysis in this study uses multiple linear regression analysis. The results of this study indicate that firm size has an effect on tax aggressiveness, while capital intensity